Whole-body vibration training: Metabolic cost of synchronous, side-alternating or no vibrations - Gojanovic, B.; Henchoz, Y. (Journal of Sports Sciences, 2012)
Whole-body vibration training improves strength and can increase maximal oxygen consumption (VO2max). No study has compared the metabolic demand of synchronous and side-alternating whole-body vibration. We measured VO2 and heart rate during a typical synchronous or side-alternating whole-body vibration session in 10 young female sedentary participants. The 20-min session consisted of three sets of six 45-s exercises, with 15 s recovery between exercises. Three conditions wererandomly tested on separate days: synchronous at 35 Hz and 4 mm amplitude, side-alternating at 26 Hz and 7.5 mm amplitude (peak acceleration matched at 20 g in both vibration conditions), and no vibrations. Mean VO2 (expressed as %VO2max) did not differ between conditions: 29.7 ± 4.2%, 32.4 ± 6.5%, and 28.7 ± 6.7% for synchronous, side-alternating, and no vibrations respectively (P = 0.103). Mean heart rate (% maximal heart rate) was 65.6 ± 7.3%, 69.8 ± 7.9%, and 64.7 ± 5.6% for synchronous, side-alternating, and no vibrations respectively, with the side-alternating vibrations being significantly higher (P = 0.019). When analysing changes over exercise sessions, mean VO2 was higher for side-alternating (P < 0.001) than for synchronous and no vibrations. In conclusion, side-alternating whole-body vibration elicits higher heart rate responses than synchronous or no vibrations, and could elevate VO2, provided the session lasts more than 20 min.